Electrocatalytic Biosynthesis using a Bucky Paper Functionalized by [Cp*Rh(bpy)Cl]+ and a Renewable Enzymatic Layer. Issue 18 (26th July 2018) - Zhang, Lin; Etienne, Mathieu; Vilà, Neus; Le, Thi Xuan Huong; Kohring, Gert‐Wieland; Walcarius, Alain
Abstract: A bioelectrode for electroenzymatic synthesis was prepared, combining a layer for NADH regeneration and a renewable layer for enzymatic substrate reduction. The covalent immobilization of a rhodium complex mediator ([Cp*Rh(bpy)Cl] + ) on the surface of a bucky paper electrode was achieved by following an original protocol in two steps. A bipyridine ligand was first grafted on the electrode by electro‐reduction of bipyridyl diazonium cations generated from 4‐amino‐2, 2′‐bipyridine, and the complex was then formed by reaction with [RhCp*Cl2 ]2 . A turnover frequency of 1.3 s −1 was estimated for the electrocatalytic regeneration of NADH by this immobilized complex, with a Faraday efficiency of 83 %. The bucky paper electrode was then overcoated by a bio‐doped porous layer made of glassy fibers with immobilized D‐sorbitol dehydrogenase. This assembly allowed for the efficient separation of the enzyme and the rhodium catalyst, which is a prerequisite for effective bioelectrocatalysis with such bioelectrochemical system, while allowing effective mass transport of NAD + /NADH cofactor from one layer to the other. Thereby, it was possible to reuse the same mediator‐functionalized bucky paper with three different enzyme layers. The bioelectrode was applied to the electroenzymatic reduction of D‐fructose to D‐sorbitol. A turnover frequency of 0.19 s −1 for the rhodium complex was observed in the presence of 3 mM D‐fructose and a total turnover number higher than 12000 was estimated. Abstract : A bioelectrode for electroenzymatic synthesis was prepared, combining a layer for NADH regeneration with immobilized [Cp*Rh(bpy)Cl] + complex and a renewable layer for enzymatic substrate reduction with immobilized dehydrogenase.